An Ovine Model of Hemorrhagic Shock and Resuscitation, to Assess Recovery of Tissue Oxygen Delivery and Oxygen Debt, and Inform Patient Blood Management. Issue 6 (December 2021) - Dyer, Wayne B.; Tung, John-Paul; Li Bassi, Gianluigi; Wildi, Karin; Jung, Jae-Seung; Colombo, Sebastiano Maria; Rozencwajg, Sacha; Simonova, Gabriela; Chiaretti, Sara; Temple, Fergal T.; Ainola, Carmen; Shuker, Tristan; et al.
ABSTRACT: Background: Aggressive fluid or blood component transfusion for severe hemorrhagic shock may restore macrocirculatory parameters, but not always improve microcirculatory perfusion and tissue oxygen delivery. We established an ovine model of hemorrhagic shock to systematically assess tissue oxygen delivery and repayment of oxygen debt; appropriate outcomes to guide Patient Blood Management. Methods: Female Dorset-cross sheep were anesthetized, intubated, and subjected to comprehensive macrohemodynamic, regional tissue oxygen saturation (StO2 ), sublingual capillary imaging, and arterial lactate monitoring confirmed by invasive organ-specific microvascular perfusion, oxygen pressure, and lactate/pyruvate levels in brain, kidney, liver, and skeletal muscle. Shock was induced by stepwise withdrawal of venous blood until MAP was 30 mm Hg, mixed venous oxygen saturation (SvO2 ) < 60%, and arterial lactate >4 mM. Resuscitation with PlasmaLyte® was dosed to achieve MAP > 65 mm Hg. Results: Hemorrhage impacted primary outcomes between baseline and development of shock: MAP 89 ± 5 to 31 ± 5 mm Hg ( P < 0.01), SvO2 70 ± 7 to 23 ± 8% ( P < 0.05), cerebral regional tissue StO2 77 ± 11 to 65 ± 9% ( P < 0.01), peripheral muscle StO2 66 ± 8 to 16 ± 9% ( P < 0.01), arterial lactate 1.5 ± 1.0 to 5.1 ± 0.8 mM ( P < 0.01), and base excess 1.1 ± 2.2 to −3.6 ± 1.7 mM ( P < 0.05). Invasive organ-specific monitoring confirmed reduced tissue oxygen delivery; oxygen tension decreased and lactate increased in all tissues, but moderately in brain. Blood volume replacement with PlasmaLyte® improved primary outcome measures toward baseline, confirmed by organ-specific measures, despite hemoglobin reduced from baseline 10.8 ± 1.2 to 5.9 ± 1.1 g/dL post-resuscitation ( P < 0.01). Conclusion: Non-invasive measures of tissue oxygen delivery and oxygen debt repayment are suitable outcomes to inform Patient Blood Management of hemorrhagic shock, translatable for pre-clinical assessment of novel resuscitation strategies. Abstract : Supplemental Digital Content is available in the text